Swedish Acquisitions With A Long-Term Perspective. Comparing the Performance of Single and Serial Acquirers. - Hulmi,Fanny Aleksandra; Lovato,Alessia (2023)
This study examines the long-term post-acquisition performance of acquirers, both serial and single, in Sweden within a time frame spanning from 2000 to 2022. The post-acquisition performance is evaluated using a long-term event study, employing the Buy-and-Hold Abnormal Returns (BHAR) methodology. The results of the 1-year BHAR analysis indicate that, on average, Swedish acquirers exhibit abnormal returns of -20.22%, indicating a trend of value destruction for acquiring firms’ shareholders in the long term. The findings of the 6-month BHAR analysis further confirm the presence of negative abnormal returns. Additionally, the study does not yield substantial evidence to establish the outperformance of either single or serial acquirers in the long run. Regression analysis incorporating deal-specific control variables does not uncover statistically significant results.
Keywords: M&A; acquisitions; serial acquirers; long-term performance; BHAR.